Perbandingan Isometrik Handgrip Exercise dan Jalan Kaki Terhadap Tekanan Darah pada Pasien Hipertensi di Puskesmas Sekip Palembang: Penelitian - Yora Nopriani; Amalia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
According to WHO data, hypertension affects about 1.28 billion adults aged 30–79 worldwide. Its management includes pharmacological and non-pharmacological therapies, such as isometric handgrip and walking.The purpose of this study was to determine the effectiveness of diabetes exercise in reducing blood glucose levels in patients with diabetes mellitus at Multiwahana Public Health Center, Palembang in 2025. This research used a pre-experimental design with a one-group pretest-posttest approach. The population in this study included all elderly patients with diabetes mellitus aged 45–60 years at Multiwahana Public Health Center, Palembang, during May 2025. The sample consisted of 30 respondents selected using purposive sampling. The research results showed that the majority of respondents had normal random blood glucose levels before the diabetes exercise, with 23 respondents (76.7%) categorized as normal, and after the exercise, 20 respondents (66.7%) remained in the normal category. Statistical tests revealed that diabetes exercise was effective in reducing blood glucose levels in patients with diabetes mellitus at Multiwahana Public Health Center, Palembang, in 2025, with a p-value = 0.000.